1998
DOI: 10.1029/97jd03737
|View full text |Cite
|
Sign up to set email alerts
|

A critical analysis of the Stratospheric Aerosol and Gas Experiment II spectral inversion algorithm

Abstract: Abstract. The ozone long-term trends derived from the Stratospheric Aerosol and Gas Experiment II have been shown to be biased by the level of volcanic aerosol. We have investigated the spectral algorithm used to separate the partial optical thicknesses associated with ozone and aerosols. We present two possible causes of inaccuracies capable of producing relative errors on the slant path ozone optical thickness as large as 5-15%. The first one is related to the interpolation of the aerosol optical thickness a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2000
2000
2003
2003

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 12 publications
0
4
0
Order By: Relevance
“…The problem of retrieving species density profiles from the measured intensity data can be divided into two distinct steps (e.g., Kyrölä et al, 1993;Fussen et al, 1997;Fussen, 1998): First, transmission data from a number of wavelength channels are used in a "spectral inversion" in order to estimate the composition of the atmospheric gas for each individual sounding ray, i.e., for each tangent height. Having subsequently performed this for all rays (data points) of an occultation event, this yields along-ray columnar content profiles for all species included.…”
Section: Introductionmentioning
confidence: 99%
“…The problem of retrieving species density profiles from the measured intensity data can be divided into two distinct steps (e.g., Kyrölä et al, 1993;Fussen et al, 1997;Fussen, 1998): First, transmission data from a number of wavelength channels are used in a "spectral inversion" in order to estimate the composition of the atmospheric gas for each individual sounding ray, i.e., for each tangent height. Having subsequently performed this for all rays (data points) of an occultation event, this yields along-ray columnar content profiles for all species included.…”
Section: Introductionmentioning
confidence: 99%
“…Since the spectral variation of the 16 showed that the application of the Angstrom law to SAGE II aerosol extinction data could result in errors of 5-10 % in the extinction coefficient. According to the estimates given by Fussen 6 the operational SAGE II algorithm yields a 5-15% error in aerosol extinction at a wavelength of 0.6 µm. He showed how a cubic fit to the aerosol extinction spectral dependence could give noticeably better results.…”
Section: Review Of Available Methodsmentioning
confidence: 99%
“…The aerosol optical depth parameterization described in was selected to keep the inversion linear. Fussen [1998] has shown that a polynomial interpolation of aerosol extinction with wavelength is preferable to methods that implicitly attempt to solve for the parameters of the underlying aerosol size distribution. For the nitrogen dioxide channels, a second order fit is done using the aerosol extinctions at 385, 441, and 521 nm, and for the midvisible ozone channels, a third order fit is done using the aerosol extinctions at 441, 521, 676, and 756 nm.…”
Section: Inversionmentioning
confidence: 99%
“…Previous studies [e.g., Steele and Turco , 1997a; Fussen , 1998] have shown that SAGE II retrievals of ozone are susceptible to biases related to the level of volcanic aerosol. The problem stems from uncertainty in separating the aerosol and gas contributions to the measured extinction.…”
Section: Simulated Retrievalsmentioning
confidence: 99%